Duration model for maturity gap risk management in Islamic banks. (12th February 2020) - Shah, Syed Alamdar Ali; Sukmana, Raditya; Fianto, Bayu Arie
Abstract : Purpose: The purpose of this paper is to propose models of duration for maturity gap risk management in Islamic banks. Design/methodology/approach: A thorough review of literature on duration modeling, duration measurement in Islamic banks and Shariah compliance has been conducted to set parameters to develop Shariah -compliant maturity gap risk management mechanism. Findings: Models based on durations of earning assets and return bearing liabilities using various rates of return earned and paid, benchmark rates and industry standards commonly used by Islamic and conventional banks. Practical implications: Increased Shariah compliance has threefold impact. Firstly, it will increase trust of customers. Secondly, it will help improve profitability by reducing non- Shariah compliance penalties from the regulators. And finally, it will enhance market capitalization and returns stability to investors because of enhanced customer base, increased level of trust and increased profitability. Originality/value: This research proposes Shariah -compliant maturity gap risk management models based on the concept of duration according to recommendations of Bank for International Settlements. As there is no such maturity gap risk management mechanism that meets the requirements of Shariah using benchmarks that are common between Islamic and conventional banks; therefore, this research presents risk management solutions that can be applied simultaneously in the entire banking sector.